2012
DOI: 10.1093/mp/sss017
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Spectroscopic Study of Chromophore–Protein Interactions in the Pr Ground State of Plant Phytochrome A

Abstract: Despite extensive study, the molecular structure of the chromophore-binding pocket of phytochrome A (phyA), the principal photoreceptor controlling photomorphogenesis in plants, has not yet been successfully resolved. Here, we report a series of two-dimensional (2-D) magic-angle spinning solid-state NMR experiments on the recombinant N-terminal, 65-kDa PAS-GAF-PHY light-sensing module of phytochrome A3 from oat (Avena sativa), assembled with uniformly 13C- and 15N-labeled phycocyanobilin (u-[13C,15N]-PCB-As.ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 76 publications
2
56
0
Order By: Relevance
“…As we have shown, the 1 H– 13 C MELODI–HETCOR data of Cph1 and oat phyA3 offered an insight into Pr structural heterogeneity at an atomic level, namely two Pr isoforms ( Pr‐I and Pr‐II ) in terms of their hydrogen‐bonding networks and charge distribution patterns around the chromophore (Fig. ).…”
Section: Mas Nmr Studies On Canonical Phytochromesmentioning
confidence: 75%
See 2 more Smart Citations
“…As we have shown, the 1 H– 13 C MELODI–HETCOR data of Cph1 and oat phyA3 offered an insight into Pr structural heterogeneity at an atomic level, namely two Pr isoforms ( Pr‐I and Pr‐II ) in terms of their hydrogen‐bonding networks and charge distribution patterns around the chromophore (Fig. ).…”
Section: Mas Nmr Studies On Canonical Phytochromesmentioning
confidence: 75%
“…It should be noted that the A ‐ring region of the cofactor in both cases is also found to show more than one conformation ( e.g . the ethylidene substituent) as well as the alternative side‐chain conformations adopted by several amino acids in the N‐terminal region . Hence, it is in principal possible that there are more isomers present, if the two regions involved could change independently, an Occam's razor explanation of the data is that two Pr isoforms coexist in the solution.…”
Section: Mas Nmr Studies On Canonical Phytochromesmentioning
confidence: 99%
See 1 more Smart Citation
“…MAS NMR at T c revealed that the Pr ground state of Cph1 comprises two isoforms, Pr‐I and Pr‐II, the latter being equivalent to the 2VEA crystal structure . A similar dimorphism is seen for oat phyA3 in the Pr state . It should be noted that a potential effect of the transmitter domain is negligible: The C‐terminus has no effect on spectroscopic and photochemical properties of the pigment as compared with Cph1Δ2; full‐length Cph1 was also shown to be heterogeneous .…”
Section: Introductionmentioning
confidence: 81%
“…Given the difficulty to rationalize color-tuning in microbial and animal rhodopsins, which depend on the 'simpler' chromophore retinal, it is not surprising that theoretical approaches such as full-scale quantum chemical and QM/MM calculations on complex bilin chromophores in their protein environment are still in their infancy [49][50][51]. Here, progress is not only impeded by radiation effects on the chromophore during structural analyses [23 ,52], but also by intrinsic conformational heterogeneity of the P r state and [53][54][55][56] and to some extent also the P fr state [57]. The second issue is the chosen mode of downstream signaling, which apparently differs in the family of phytochrome-like photoreceptors (Figure 4c and d).…”
Section: Discussionmentioning
confidence: 99%